Krizová orální historie: k terénnímu výzkumu v čase krizí - Jiří Hlaváček (Studia Ethnologica Pragensia, 2022)
The overview study focuses on a closer presentation of the dynamically developing interdisciplinary direction within oral history in recent years. The so-called crisis oral history focuses on documenting the actor’s reflection of survivors or eyewitnesses of extreme, crisis or otherwise traumatic events, during or shortly after their end. The author first presents a brief development of crisis oral history and a varied range of research topics (war conflicts, suppression of human rights, natural disasters, mass disasters, terrorist attacks, forced migration, pandemics, etc.) from the first half of the last century to the present day, including key milestones such as terrorist attacks from September 11, 2001 or the recent coronavirus pandemic. Attention is also paid to the theoretical, methodological and ethical aspects of crisis field research (including challenges and possible pitfalls) with an emphasis on the issue of traumatic memories within oral-historical interviews.